2005
DOI: 10.1016/j.femsre.2005.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic K+channels: From crystal structures to diversity

Abstract: The deep roots and wide branches of the K(+)-channel family are evident from genome surveys and laboratory experimentation. K(+)-channel genes are widespread and found in nearly all the free-living bacteria, archaea and eukarya. The conservation of basic structures and mechanisms such as the K(+) filter, the gate, and some of the gate's regulatory domains have allowed general insights on animal K(+) channels to be gained from crystal structures of prokaryotic channels. Since microbes are the great majority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
94
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 153 publications
1
94
0
Order By: Relevance
“…Traditional methods for analyzing prokaryotic ion channels rely on recombinant expression in E. coli, affinity purification, and reconstitution into either lipid bilayers for electrophysiological analysis or into liposomes for macroscopic ion flux studies (10,11,13,14). A recent study (7) also reported successful expression of KcsA in mammalian cells using a codon-optimized synthetic gene.…”
Section: Identification and Cloning Of The Kirbac Superfamilymentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional methods for analyzing prokaryotic ion channels rely on recombinant expression in E. coli, affinity purification, and reconstitution into either lipid bilayers for electrophysiological analysis or into liposomes for macroscopic ion flux studies (10,11,13,14). A recent study (7) also reported successful expression of KcsA in mammalian cells using a codon-optimized synthetic gene.…”
Section: Identification and Cloning Of The Kirbac Superfamilymentioning
confidence: 99%
“…Many of the recent advances in our understanding of K ϩ channel structure and function have been achieved through the study of prokaryotic homologs (11,13,14). But although many of these prokaryotic K ϩ channels share extensive homology with mammalian channels in the "transmembrane pore" region, their homology outside of this region is less well defined, e.g., the KcsA K ϩ channel from Streptomyces lividans, which has proven so useful in determining the mechanism of K ϩ permeation and channel gating, has no obvious mammalian counterpart.…”
mentioning
confidence: 99%
“…R egulator of K þ conductance (RCK) domains control the activity of a variety of K þ channels and transporters, including the prokaryotic TrkA/H K þ transport complex and the eukaryotic large-conductance calcium-activated (BK) channel, through binding of cytoplasmic ligands such as ATP, H þ and Ca 2 þ (refs [1][2][3][4][5][6][7][8]. Thus, RCK domains transduce ligand binding to gate transmembrane K þ flux in response to signalling events and cellular metabolism, in organisms ranging from bacteria to humans.…”
mentioning
confidence: 99%
“…calcium | lipid bilayer | cooperativity R egulator of K þ conductance (RCK) domains are structurally conserved ligand-binding domains that control the activity of a diverse array of K þ channels and transporters (1)(2)(3). Many prokaryotic RCK domains contain a conserved sequence motif for binding of nucleotides (NAD þ or ATP) (4,5).…”
mentioning
confidence: 99%